Depression and hopelessness in patients with acute leukemia: the psychological impact of an acute and life‐threatening disorder. Issue 8 (18th September 2015) - Gheihman, Galina; Zimmermann, Camilla; Deckert, Amy; Fitzgerald, Peter; Mischitelle, Ashley; Rydall, Anne; Schimmer, Aaron; Gagliese, Lucia; Lo, Chris; Rodin, Gary
Abstract: Objective: Acute leukemia (AL) is a life‐threatening cancer associated with substantial morbidity and mortality, particularly in older adults. Given that there has been little research on the psychological impact of such malignancies with acute onset, we assessed the prevalence and correlates of depression and hopelessness in patients with AL. Methods: Three hundred forty‐one participants were recruited within 1 month of diagnosis or relapse and completed the Beck Depression Inventory‐II (BDI‐II), Beck Hopelessness Scale (BHS), Memorial Symptom Assessment Scale, and other psychosocial measures. Multivariate regression analyses identified correlates of depression and hopelessness. Results: 17.8% reported clinically significant depressive symptoms (BDI‐II ≥ 15), 40.4% of which were in the moderate‐severe range (BDI‐II ≥ 20). 8.5% reported significant symptoms of hopelessness (BHS ≥ 8). Depression was associated with greater physical symptom burden (adjusted R 2 = 48.4%), while hopelessness was associated with older age and lower self‐esteem (adjusted R 2 = 45.4%). Both were associated with poorer spiritual well‐being. Conclusions: Clinically significant depressive symptoms were common early in the course of AL and related to physical symptom burden. Hopelessness was less common and associated with older age and lower self‐esteem. The results suggest that whereas depression in AL may be related to disease burden, the preservation of hope may be linked to individual resilience, life stage, and realistic prognosis.Copyright © 2015 John Wiley & Sons, Ltd.